Antigenic variation in the phase I lipopolysaccharide of Coxiella burnetii isolates. - Hackstadt, T (1986)
Coxiella burnetii isolates from a variety of clinical and geographical sources were screened for antigenic variation of lipopolysaccharides (LPSs) by sodium dodecyl sulfate-polyacrylamide gel electrophoresis coupled with silver staining or immunoblotting. All isolates from chronic Q fever or other sources possessed a phase I-type LPS. These LPSs appeared to fall into three groups based on the sodium dodecyl sulfate-polyacrylamide gel electrophoresis profile or on reactivity with rabbit anti-C. burnetti antisera. The LPS of one group was identified on isolates from milk, ticks, or primary Q fever. The two remaining groups were found almost exclusively on isolates from human cases of chronic Q fever.